2017
DOI: 10.1002/bmb.21050
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to enhance the teaching quality of experimental biochemistry for MBBS students in TSMU, China

Abstract: With the internationalization of medical education in China, the importance of international students' education in medical schools is also increasing. Except foreign students majoring in Chinese language, English Bachelor of Medicine, Bachelor of Surgery (MBSS) students are the largest group of international students. Based on problems in the teaching process for experimental biochemistry, we designed teaching models adapted to the background of international students and strengthened teachers' teaching abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Our study has shown results better than we expected, but the achieved target was lower compare of our study compare to this study; that is between 60% and 70%. 13 Shifa Tameer-e-Millat University (STMU) has tried to adapt international clinical education curriculum inside the subsequent 5-year developmental plan. The BP Koirala University of Health Sciences in Nepal and India is known for its academic excellence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has shown results better than we expected, but the achieved target was lower compare of our study compare to this study; that is between 60% and 70%. 13 Shifa Tameer-e-Millat University (STMU) has tried to adapt international clinical education curriculum inside the subsequent 5-year developmental plan. The BP Koirala University of Health Sciences in Nepal and India is known for its academic excellence.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hence, the importance of sound and practical knowledge in the education of clinical college students has become inevitable to ignore especially in Biochemistry. 2 Genetics is an integral part of Biochemistry. The research and advancements in genetics make it impossible to ignore in clinical medicine.…”
Section: Introductionmentioning
confidence: 99%
“…These contents are close to the contemporary life of Chinese people and depict a new and real China to foreigners; at the same time, these contents are also the hot topics in which Chinese learners are most interested. The use of short videos of foreigners in China in classroom teaching can help Chinese learners further understand and understand contemporary Chinese society and culture (Yu et al, 2017). 2.…”
Section: Short Video Caption Generation Depth Model Algorithmmentioning
confidence: 99%
“…Attendance is usually considered important for learning efficiency (24). Thus we analyzed the absence rate, expressed as percentage of lecture attendance by each student and its correlation with the final score.…”
Section: Correlation Of Final Scores With Absence Ratesmentioning
confidence: 99%